2021
DOI: 10.1101/2021.01.25.21249684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Home-based management of COVID-19 by identification of low-risk features

Abstract: BackgroundCovid-19 is a triphasic disorder characterized by a viral phase lasting 7-10 days from onset of symptoms. In approximately 20% it is followed by a second stage heralded by elevation of pro- inflammatory markers such as ferritin, IL-6, CRP, LDH and D-dimers. We hypothesized that those with few abnormalities would have a low risk for progression to respiratory insufficiency and hence could be monitored at home without treatment.MethodsInclusion criteria included Covid infection, age >21, Oxygen satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although number of studies have already shown the association of COVID-19 severity with CRP and D-dimer levels in blood, there are limited studies done on Bangladeshi populations (Chowdhury et al, 2020;Khourssaji et al, 2020;Velavan and Meyer, 2020;Cabanillas et al, 2021;Synolaki et al, 2021). In a recent study done by (Ullah et al, 2020), both high D-Dimer (>501 ng/ml) and high CRP (>101 mg/dl) were associated with increased need for upgrade to the ICU and higher requirement for (intermittent mandatory ventilation) IMV on day-7 of hospitalization (Soraya and Ulhaq, 2020;Ullah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although number of studies have already shown the association of COVID-19 severity with CRP and D-dimer levels in blood, there are limited studies done on Bangladeshi populations (Chowdhury et al, 2020;Khourssaji et al, 2020;Velavan and Meyer, 2020;Cabanillas et al, 2021;Synolaki et al, 2021). In a recent study done by (Ullah et al, 2020), both high D-Dimer (>501 ng/ml) and high CRP (>101 mg/dl) were associated with increased need for upgrade to the ICU and higher requirement for (intermittent mandatory ventilation) IMV on day-7 of hospitalization (Soraya and Ulhaq, 2020;Ullah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although number of studies have already shown the association of COVID-19 severity with CRP and Ddimer levels in blood, there are limited studies done on Bangladeshi populations (5,6,7,8,9). In a recent study done by Ullah, Waqas et al [2] both high D-Dimer (> 501 ng/ml) and high CRP (> 101 mg/dl) were associated with increased need for upgrade to the ICU and higher requirement for (intermittent mandatory ventilation) IMV on day-7 of hospitalization (2,25).…”
Section: Introductionmentioning
confidence: 99%